Beauveria bassiana Vuill. (Ascomycetes: Clavicipitaceae) sobre Thaumastocoris peregrinus Carpinteiro & Dellapé (Hemiptera: Thaumastocoridae) - Ribeiro, Raquel Rossi (2016)
The bronze bug of eucalyptus, Thaumastocoris peregrinus, is a phytophagous insect that causes yellowness of leaves of Eucalyptus, and in severe cases, death, and defoliation of plants. Forms of natural control and/or biological control for this insect are aimed. In this perspective, biological control has been increasing and the use of entomopathogenic fungi is feasible, as already occurs naturally in the environment. In this sense, it aimed to evaluate the action of entomopathogenic fungus B. bassiana, isolated IBCB 66 on different developmental stages of T. peregrinus in laboratory conditions. The treatments were: sterilized distilled water (SDW), Distilled water Tween 80 (0.01%) (DWT) and B. bassiana IBCB 66 (1.0 x 108 conidia mL-1). These treatments were evaluated in three bioassays in experimental design. 1: B. bassiana action on eggs of T. peregrinus: Eucalyptus benthamii leaves were cut into disks of 2.4 cm Ø, allocated within flat glass tubes (2.5 cm Ø and 10 cm h). Cards containing on average 10 eggs of T. peregrinus were immersed in the solution corresponding to each treatment and placed on leaf discs a total of 20 replications / treatment, and kept in a climatized chamber BOD (27 ± 2 ° C, 14 h photoperiod and RH 70 ± 10%) (standard procedure for all bioassays). They evaluated the incubation period and the viability of T. peregrinus eggs. 2: B. bassiana action on nymphs of T. peregrinus: E. benthamii discs of 2.4 cm Ø, pretreated were placed inside glass tubes that received following a nymph 3° instar T. peregrinus totaling 50 tubes / replications. In this bioassay were evaluated duration and viability of the nymphal instars. 3: B. bassiana action on adults of T. peregrinus: This bioassay was performed as described methodology for nymphs. Each glass tube received an adult T. peregrinus, totaling 50 tubes / replications per treatment. In this bioassay was assessed daily longevity to the total mortality of insects. Some adult specimens dead who came into contact with B. bassiana were collected for histologic analysis as standard methodology. B. bassiana did not affect the incubation period and viability of eggs of T. peregrinus. The same was observed on nymphs of 3° instar and adults who have not had the studied biological parameters affected by the fungus. The average duration and viability were reduced by 4 ° to 5 ° instar nymphs , indicating that the pathogen is B. bassiana this development phase. Histological examination of the adults of T. peregrinus verified the presence of hyphae, conidia and conidiophores in the digestive system and muscle tissues.